2010
DOI: 10.1111/j.1472-765x.2010.02979.x
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination efficacy against Mycoplasma

Abstract: Aims:  Mycoplasma is minute bacteria that can be found ubiquitously in the environment and also in human, animal and plant tissues. In addition to their public health importance as aetiological agents of infections and possible association with certain cancers, mycoplasma is a major contamination concern in biotechnology. These bacterial cells are very small, can form biofilms and survive for extended periods of time when dried onto surfaces. Despite these concerns, there is little information concerning their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…One study presented with an unclear risk for incomplete data representation or outlier results being present [ 12 ]. Confounding variables for selection bias was of unknown risk for eight of the articles [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Incomplete data presentation leading to attrition bias or at least the risk of misinterpretation of the log loss of viruses were not determined due to the various steps of virus remuneration after VHP exposure [ 12 , 14 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study presented with an unclear risk for incomplete data representation or outlier results being present [ 12 ]. Confounding variables for selection bias was of unknown risk for eight of the articles [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Incomplete data presentation leading to attrition bias or at least the risk of misinterpretation of the log loss of viruses were not determined due to the various steps of virus remuneration after VHP exposure [ 12 , 14 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Certain studies recognized the loss of the pathogens during the methodology and reported on the log reduction determined in the studies for viruses [ 16 , 24 , 25 ] and bacteria [ 13 , 26 ]. The loss of pathogens has been specifically noted with viruses [ 25 ] but has also occurred with bacteria [ 13 ] on dry surfaces indicated at each step of the methodology with reconstitution and neutralization. The assessment of the lost pathogens provides transparency to the research.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it should be noted that Mycoplasma and SARS-CoV-2 (Eterpi et al .) [ 27 ] and SARS-CoV-2 are completely inactivated by ethanol. Moreover, certain strains of Clostridia are known to produce endogenous ethanol and this potential has been exploited industrially in ABE fermentation (acronym) to produce acetone, butanol and ethanol [ 28 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…Once morphologically identified, ticks were stored at −20 • C until further examination. Each tick was bathed in 70% ethanol for 5 min [31] and divided lengthwise into two parts in sterile Petri dishes under the stereomicroscope, using sterile forceps and scalpels: One half was screened by cultural and molecular methods, with the remaining half kept in alcohol, pending further investigation. Ticks belonging to the same species and stage, and derived from the same animal, were analyzed in pools.…”
Section: Tick Identificationmentioning
confidence: 99%